Hubungan stres, kecemasan, dan depresi dengan kualitas tidur siswa SMA di Gresik dalam menghadapi ujian akhir semester - Putri, Herlina Tiara; Widiyawati, Wiwik (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Sleep quality is a common phenomenon that occurs in society which can be caused by anxiety, depression, stress that is felt. Sleep quality is a person's sleep condition to get fitness when waking up. Purpose: To determine the relationship between stress, anxiety, and depression with the quality of sleep of high school students in Gresik in facing the final semester exams. Method: Quantitative research with a cross-sectional approach involving students of SMA X and conducted on November 19, 2024. The sample selection used the slovin formula with simple random sampling and obtained 179 students as samples with inclusion criteria including, high school students aged 15-18 years and willing to be respondents. Data collection using two questionnaires, namely DASS 21 (as a tool to measure symptoms of depression, anxiety, and stress) and the Pittsburgh Sleep Quality Index (PSQI) as a measure of the level of student sleep disturbance. Results: The majority of respondents experienced moderate sleep disturbances as many as 104 (58.1%) with normal stress levels as many as 171 respondents (95.5%), normal anxiety as many as 108 respondents (60.3%), and normal depression as many as 152 (84.9%). The results of statistical test analysis of each variable showed a p value <0.05, so it can be interpreted that there is a relationship between stress, anxiety, and depression with the quality of sleep of students. Conclusion: There is a significant relationship between stress, anxiety, and depression with the quality of sleep of students facing the final semester exams. Suggestion: To the school to be able to provide sleep hygiene education, attention, and motivation to students to be able to improve their sleep quality properly. Keywords: Anxiety; Depression; Sleep Quality; Stress. Pendahuluan: Kualitas tidur merupakan fenomena yang sering terjadi di masyarakat yang dapat disebabkan karena kecemasan, depresi, stres yang dirasakan. Kualitas tidur merupakan kondisi tidur seseorang untuk mendapatkan kebugaran saat seseorang tersebut terbangun dari tidurnya. Tujuan: Untuk mengetahui hubungan stres, kecemasan, dan depresi dengan kualitas tidur siswa SMA di Gresik dalam menghadapi ujian akhir semester. Metode: Penelitian kuantitatif dengan pendekatan cross-sectional yang melibatkan para siswa/siswi SMA X dan dilakukan pada tanggal 19 November 2024. Pemilihan sampel menggunakan rumus slovin dengan simple random sampling dan didapatkan sebesar 179 siswa/siswi sebagai sampel dengan kriteria inklusi meliputi, siswa/siswi SMA berusia 15-18 tahun dan bersedia menjadi responden. Pengambilan data menggunakan dua kuesioner yaitu DASS 21 (sebagai alat mengukur gejala depresi, rasa cemas, dan stres) dan Pittsburgh Sleep Quality Indeks (PSQI) sebagai pengukur tingkat gangguan tidur siswa. Hasil: Mayoritas responden mengalami gangguan tidur sedang sebanyak 104 (58.1%) dengan tingkat stress normal sebanyak 171 responden (95.5%), kecemasan normal sebanyak 108 responden (60.3%), dan depresi normal sebanyak 152 (84.9%). Hasil analisis uji statistik dari masing-masing variabel menunjukkan nilai p <0.05, sehingga dapat diartikan adanya hubungan antara stress,kecemasan, dan depresi dengan kualitas tidur para siswa/siswa. Simpulan: Terdapat hubungan yang signifikan antara stress, kecemasan, dan depresi dengan kualitas tidur para siswa/siswi dalam menghadapi ujian akhir semester. Saran: Kepada pihak sekolah untuk bisa memberikan edukasi sleep hygiene, perhatian, dan motivasi kepada para siswa/siswi untuk bisa meningkatkan kualitas tidur mereka dengan baik. Kata Kunci: Depresi; Kecemasan; Kualitas Tidur; Stres.